Engineering Large In-Plane Tensile Strains in Ge Microdisks, Microrings and Racetrack Optical Cavities. (18th August 2016) - Millar, Ross; Gallacher, Kevin; Frigerio, Jacopo; Ballabio, Andrea; Bashir, Aneeqa; MacLaren, Ian; Isella, Giovanni; Paul, Douglas J
Abstract : Highly strained Ge micro-cavities are demonstrated, with biaxial equivalent tensile strains > 2 % at the top surface, demonstrating photoluminescence up to the detector cut-off of 2.5 µm wavelength. Ge on Si micro-disk, rings, and racetrack structures are investigated, which have been undercut by wet etching techniques. The anisotropy of the wet etch in the Si leads to the realization of novel, partially suspended structures. The strain distributions in the different cavity structures are discussed and compared with regard to the in-plane uniformity, peak strain level, and effect of the strain distribution on the Ge band-structure.